2019
DOI: 10.1016/j.artint.2018.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Learning tractable Bayesian networks in the space of elimination orders

Abstract: The computational complexity of inference is now one of the most relevant topics in the field of Bayesian networks. Although the literature contains approaches that learn Bayesian networks from high dimensional datasets, traditional methods do not bound the inference complexity of the learned models, often producing models where exact inference is intractable. This paper focuses on learning tractable Bayesian networks from data. To address this problem, we propose strategies for learning Bayesian networks in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Nevertheless, the BN community has some opensource software packages that are well maintained and have a good extensibility; however, they are designed for highly specific tasks, e.g. learning algorithms (Aragam et al, 2019; Benjumeda et al, 2019) and inference algorithms (Højsgaard, 2012). We also have other packages, such as bnlearn (Scutari, 2010) and pgmpy (Ankan and Panda, 2015), which comprise a set of interconnected tools but they lack some basic modules, e.g., a graphical interface or connection with other packages, which would make them to be considered as frameworks.…”
Section: Problems With State-of-the-art Of Software In Massive Bn Intmentioning
confidence: 99%
“…Nevertheless, the BN community has some opensource software packages that are well maintained and have a good extensibility; however, they are designed for highly specific tasks, e.g. learning algorithms (Aragam et al, 2019; Benjumeda et al, 2019) and inference algorithms (Højsgaard, 2012). We also have other packages, such as bnlearn (Scutari, 2010) and pgmpy (Ankan and Panda, 2015), which comprise a set of interconnected tools but they lack some basic modules, e.g., a graphical interface or connection with other packages, which would make them to be considered as frameworks.…”
Section: Problems With State-of-the-art Of Software In Massive Bn Intmentioning
confidence: 99%
“…The time complexity of tractable SEM is highly sensitive to the computational cost of searching for low-width EOs. Benjumeda et al [55] demonstrated that elimination trees (ETs) [56] can be used to implement an efficient heuristic for this problem. In this section, we apply their approach to search for low-width EOs.…”
Section: Efficient Search Of Low-width Elimination Ordersmentioning
confidence: 99%
“…Circumventing this redundancy reduces the size of the search space during the learning process. Grant and Horsch [56] proposed elimination trees (ETs), a representation for recursive conditioning, which has been adapted to exploit equivalence among EOs [55] .…”
Section: Efficient Search Of Low-width Elimination Ordersmentioning
confidence: 99%
See 1 more Smart Citation
“…To deal with this important problem, there are 2 main methods that are used to create classification methods for multi-class data: The traditional base model method and the ensemble model method. At the traditional base model method [30][31][32][33][34][35][36][37][38][39][40], the model used to classify the resultant class, such as classifying the resultant class The nature of the decision tree, which is the decision tree method [41], is used to predict the pattern recognition class of the individual base model. [5,[42][43][44] Accuracy depends on the factors of the prediction of the result of class [45].…”
Section: Introductionmentioning
confidence: 99%